Bentuk dan inklinasi eminensia artikularis serta kedalaman fossa glenoidalis berdasarkan usia ditinjau dari radiograf panoramikMorphology and inclination of articular eminence and glenoid fossa depth based on age observed in panoramic radiograph - Salsabila Afnia; Azhari Azhari; Farina Pramanik (Padjadjaran Journal of Dental Researchers and Students, 2022)
ABSTRAK Pendahuluan: Perubahan bentuk, ukuran eminensia artikularis dan fossa glenoidalis selama masa pertumbuhan perlu diketahui karena berperan penting dalam pergerakan sendi temporomandibular, sehingga membantu menegakkan diagnosa ada tidaknya kelainan pada tumbuh kembang. Variasi serta perubahan dapat dilihat dan diukur melalui radiograf panoramik. Tujuan penelitian ini untuk meneliti bentuk dan inklinasi eminensia artikularis serta kedalaman fossa glenoidalis berdasarkan usia ditinjau dari radiograf panoramik. Metode: Jenis penelitian deskriptif dengan teknik pengambilan sampel purposive sampling. Jumlah sampel didapat dengan menggunakan rumus Slovin, sebanyak 60 radiograf panoramik pasien RSGM Unpad, bulan Januari-Mei 2018 dengan rentang usia 5-30 tahun dibagi kedalam tiga kelompok usia berdasarkan usia pertumbuhan komponen temporal. Bentuk eminensia, inklinasi eminensia dan kedalaman fossa diukur menggunakan software ImageJ. Data diolah menggunakan Microsoft Excel® untuk mengetahui nilai minimum, maksimum, nilai rerata, dan standar deviasi. Hasil: Mayoritas bentuk eminensia artikularis pada tiap kelompok usia adalah sigmoid. Rerata inklinasi eminensia artikularis adalah 42°, rentang usia 5-10 tahun, 44° pada rentang usia 11-20 tahun, dan 58° pada rentang usia 21-30 tahun. Rerata kedalaman fossa glenoidalis adalah 4,62 mm pada rentang usia 5-10 tahun, 5,71 mm pada rentang usia 11-20 tahun, dan 7,52 mm pada rentang usia 21-30 tahun. Simpulan: Bentuk mayoritas eminensia artikularis selama masa pertumbuhan adalah sigmoid, serta inklinasi eminensia artikularis dan kedalaman fossa glenoidalis nilai reratanya semakin meningkat seiring dengan pertambahan usia selama masa pertumbuhan. Eminensia artikularis dan fossa glenoidalis mengalami fase pertumbuhan aktif pada rentang usia 5-10 tahun, berjalan lambat pada rentang usia 11-20 tahun, dan mengalami penyempurnaan serta perkembangan pada rentang usia 21-30 tahun.Kata kunci: sendi temporomandibular; eminensia artikularis; fossa glenoidalis; usia; radiograf panoramik ABSTRACT Introduction: Changes in the morphology and size of the articular eminence and the glenoid fossa during the growth period need to be known because it plays an essential role in the movement of the temporomandibular joint, thus helping to diagnose the presence or absence of abnormalities in the growth and development. These variations and changes can be seen and measured through panoramic radiographs. The purpose of this study was to examine the morphology and inclination of the articular eminence and the depth of the glenoid fossa based on age observed from a panoramic radiograph. Methods: This research was descriptive with a purposive sampling technique. The number of samples obtained using the Slovin formula, which resulted in 60 panoramic radiographs of the patients from Universitas Padjadjaran Dental Hospital (RSGM Unpad), during the period of January-May 2018, with an age range of 5-30 years, divided into three age groups based on the age of the temporal component growth. Eminence morphology and inclination, and fossa depth were measured using ImageJ software. The data were processed using Microsoft Excel® to determine the minimum, maximum, mean, and standard deviation values. Results: Most articular eminence morphology found in each age group were sigmoid. The mean articular eminence inclination in the age range of 5-10 years was 42°, 44° in the age range of 11-20 years, and 58° in the age range of 21-30 years. The mean of the glenoid fossa depth in the age range of 5-10 years was 4.62 mm, 5.71 mm in the age range of 11-20 years, and 7.52 mm in the age range of 21-30 years. Conclusions: Most articular eminence morphology during the growth period is sigmoid. The mean value of the articular eminence inclination and the glenoid fossa depth increases with age during the growth period. The articular eminence and glenoid fossa undergo an active growth phase in the age range of 5-10 years, progress slowly at the age range of 11-20 years, and undergo completion and development in the age range of 21-30 years.Keywords: temporomandibular joint; articular eminence; glenoid fossa; age; panoramic radiograph